Teknik Long Exposure dengan Objek Pantai Drini Gunungkidul di Malam Bulan Purnama - Nofria Doni Fitri (AKSA: Jurnal Desain Komunikasi Visual, 2022)
Photography as an objective representation of nature can serve as an illustration that describes the actual state of a natural tourist attraction. Gunungkidul has many stunning natural tourist destinations, one of which is the beach. However, the beauty of the beach is still dominated by taking pictures during the day. Natural atmosphere at night is still rarely found. In fact, nature tourism is facilitated with hotels and inns, the prices are affordable and many tourists enjoy the night atmosphere on the beach. This study offers a technique for taking pictures of Drini Beach Gunungkidul on a full moon night. Taking pictures using a Nikon D3 series DSLR Camera with a 24-85 mm nikkor lens. Obstacles in understanding rapidly changing situations, must be sensitive to the color of light, selection of ISO, aperture, shutter speed, color temperature, white balance, and determining the exposure value according to the situation at the location. Professional grade DSLR camera needed with fine grain at high ISO, experiment was carried out during full moon. This study aims to find the right formula for the technique of taking natural beach photos.